Total Synthesis of Talatisamine. Issue 1 (19th November 2019) - Kamakura, Daiki; Todoroki, Hidenori; Urabe, Daisuke; Hagiwara, Koichi; Inoue, Masayuki
Abstract: Talatisamine (1 ) is a member of the C19 ‐diterpenoid alkaloid family, and exhibits K + channel inhibitory and antiarrhythmic activities. The formidable synthetic challenge that 1 presents is due to its highly oxidized and intricately fused hexacyclic 6/7/5/6/6/5‐membered‐ring structure (ABCDEF‐ring) with 12 contiguous stereocenters. Here we report an efficient synthetic route to 1 by the assembly of two structurally simple fragments, chiral 6/6‐membered AE‐ring 7 and aromatic 6‐membered D‐ring 6 . AE‐ring 7 was constructed from 2‐cyclohexenone (8 ) through fusing an N‐ethylpiperidine ring by a double Mannich reaction. After coupling 6 with 7, an oxidative dearomatization/Diels–Alder reaction sequence generated fused pentacycle 4 b . The newly formed 6/6‐membered ring system was then stereospecifically reorganized into the 7/5‐membered BC‐ring of 3 via a Wagner–Meerwein rearrangement. Finally, Hg(OAc)2 induced an oxidative aza‐Prins cyclization of 2, thereby forging the remaining 5‐membered F‐ring. The total synthesis of 1 was thus accomplished by optimizing and orchestrating 33 transformations from 8 . Abstract : The highly oxidized and intricately fused hexacyclic structure (ABCDEF‐ring) of talatisamine with 12 contiguous stereocenters presents a formidable challenge for chemical construction. An efficient strategy, in which the entire hexacycle is assembled from a chiral AE‐ring fragment and an aromatic D‐ring, led to the total synthesis of talatisamine in 33 steps from 2‐cyclohexenone.